Legal Liability for Construction Failures In The Digital Era: A Qualitative Analysis of The Use Of Building Information Modeling (BIM) - Pandam Bayu Seto Aji; Agung Budiwirawan (Universitas Negeri Semarang, 2026)
The development of digital technology in the construction industry has led to major innovations through the implementation of Building Information Modelling (BIM), which enables cross-disciplinary collaboration within a single integrated digital model. However, this transformation also presents new legal challenges, particularly regarding the allocation of responsibility in the event of construction failures. This study aims to analyse how contractual clauses govern risk distribution associated with BIM use and how digital collaboration practices shape the determination of legal liability in real-world projects. Using a qualitative approach grounded in literature review and normative analysis, it was found that the collaborative nature of BIM blurs the traditional boundaries between designers, contractors, and project owners. The lack of clear regulations and the weak implementation of the BIM Execution Plan (BEP) often make it difficult to identify the liable party in cases of design errors or technical failures. Therefore, reformulation of contracts and regulations is required to explicitly define rights, obligations, and digital audit mechanisms to ensure legal certainty. In conclusion, the use of BIM demands comprehensive legal adaptation to balance technological efficiency and professional accountability in the era of digital construction.